Ermittlung niveaustufenspezifischer Indikatoren zur Bewertung von Textproduktionen im Rahmen der Deutschen Sprachprüfung für den Hochschulzugang (DSH) Eine Lernersprachenanalyse - Yildirim, Hülya (Universitätsverlag Göttingen, 2022)
In the context of testing and examination, the assessment of texts presents a particular challenge. Since textual competence cannot be measured directly, it is assessed indirectly via textuality criteria. In the field of foreign language testing, a target-oriented text production is set as a task; this is also the case in the DSH (Deutsche Sprachprüfung für den Hochschulzugang = German Language Test for University Entrance). DSH text productions are evaluated by means of an analytical evaluation sheet with textuality criteria and in case of passing the exam reported in three levels: DSH-1, DSH-2 and DSH-3. This paper deals with an investigation conducted on DSH text productions to determine which textuality criteria are characteristic for each DSH.